Devolution and the Development of Family Law in Wales - Osian Rees (Child and Family Law Quarterly, 2008)
This article, which is based on research undertaken on behalf of the North Wales Family Justice Council, considers the impact of devolution on the development of family and child law in Wales. The article examines key developments that have taken place to date, and considers how the position may change following the Government of Wales Act 2006, particularly in the light of the proposed Legislative Competence Order Relating to Vulnerable Children and Child Poverty. It is suggested that the divergences that are beginning to emerge between Wales and England are likely to become far more accentuated in the future.